Reversible myelopathy: An uncommon accompaniment of hypothyroidism - Nimisha Jain; Ramesh Aggarwal; Sachin Kumar Jain; Nitin Garg; Aadhaar Dhooria; Kajal Prasad (SpringerOpen, 2014)
Atypical neurological presentations of hypothyroidism include myelopathy which has been seldom reported as presenting feature in patients. This case was one of those atypical presentations of hypothyroidism in which patient presented with neurological complication viz myelopathy which was timely diagnosed and treated. The symptoms including neurological findings reversed with thyroxin replacement. The case highlights the varied and vivid manifestations of hypothyroidism which treating physicians should be aware of while treating patients.